Pengembangan Sistem Informasi Desa Untuk Meningkatkan Transparansi Administrasi Desa melalui E-Government - Indriati Amirullah; Lili Purnama Sari; Syafaruddin Syafaruddin; Muh Fadli Faisal Rasyid; HM. Adnan Lira; Nasiratunnisaa Mallappiang; Muhammad Masdar; Firman H; Nurasia Natsir (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
This community service focuses on the application of information technology in the form of e-government in Biring Ere Village, Bunggoro District, Pangkep Regency. The main objective of this activity is to increase community knowledge and motivation regarding the development of the Village Information System (SID) to increase the transparency of village administration through e-government. Through a series of lectures, tutorials and discussions, the public is taught about the importance of SID and how to use it. This activity also involved coordination with the Head of Biring Ere Village and community members. The results of this service show an increase in community knowledge and motivation about the benefits of e-government for the development of their village. Apart from that, this activity also opens up opportunities for the development and implementation of e-government in other villages in Pangkep Regency.